REORIENTASI STRATEGI PENDIDIKAN ISLAM; SEBAGAI UPAYA PENINGKATAN MUTU SUMBER DAYA MANUSIA - M. Badar (Al Hikmah: Jurnal Studi Keislaman, 2012)
Islamic Education has an important task, namely how to develop quality human resources (HR) for Muslims to take an active role and still survive in the era of globalization. Hasan Langgulung provide educational strategies to improve the quality of human resources education strategies at the macro and micro as well as giving priority actions to be given by those in charge of education in the Islamic world, especially the government. Macro strategy consists of three main components: first, the purpose of Islamic education that includes the formation of the pious man and the pious society. Second, the basic foundation upon which Islamic education curriculum consists of eight aspects: integrity, unity, continuity, originality, scientific, practical nature, solidarity, and openness. Third, the priorities in the action which includes the absorption of all children who reach school age, the diversity of development paths, review the materials and methods of education, strengthening of religious education, administration and planning, and regional cooperation between countries in the Moslem world. Whereas strategy the micro consists of only one component only, namely tazkiyah al-nafs (soul cleansing). Islamic education should have the orientation to develop human resources. In this case presents three orientations Hasan Langgulung for Islamic education in building motivation/work ethic, discipline building work, and the internalization of values.